Art and the Nazis, 1933-1945 : looting, propaganda and seizure - McLaughlin, Arthur J. (McFarland, 2021)
"This first comprehensive analysis of the Third Reich's efforts to confiscate, loot, censor and influence art begins with a brief history of the looting of artworks in Western history. The artistic backgrounds of Adolf Hitler and Hermann Goering are examined, along with the various Nazi art looting organizations, and Nazi endeavors to both censor and manipulate the arts for propaganda purposes. Long-held beliefs about the Nazi destruction of "degenerate art" are examined, drawing on recently developed university databases, new translations of original documents and recently discovered information. Theft and destruction of artworks by the Allies and looting by Soviet Trophy Brigades are also documented"--